Diagnosis and operative management of a perforated de Garengeot hernia. (2017) - Bloom, Alexi; Baio, Flavio E.; Kim, Keemberly; Fernandez-Moure, Joseph S.; Reader, Michael
Highlights: A de Garengeot hernia is a femoral hernia containing the appendix. Diagnosis of a de Garengeot hernia is difficult and often made intra-operatively. Incarceration or strangulation tends to be the clinical presentation of a de Garengeot hernia. It is important to have a high clinical suspicion for a de Garengeot hernia in patients with incarcerated or strangulated right femoral hernias. Abstract: Introduction: A de Garengeot hernia, a femoral hernia containing the appendix, is a difficult diagnosis often made intra-operatively when the hernia sac is opened. It is a rare finding, and complications are more frequent with a de Garengeot hernia. Presentation of case: A 92 year-old female presented to the emergency department (ED) complaining of abdominal pain. A computed tomographic (CT) scan of the abdomen and pelvis demonstrated a hernia anterior to the inguinal ligament without strangulation. Two weeks later the patient returned to the ED with worsening abdominal pain in the right lower quadrant. Repeat CT scan demonstrated a 7 × 4 cm complex fluid collection in the right inguinal region, and the patient was taken to the operating room for exploration. The hernia sac was entered and found to contain the appendix with evidence of distal perforation. The appendix was taken out, and the hernia defect was repaired. The patient tolerated the procedure well. Discussion: Femoral hernias have a high risk of incarceration due to the tightness of the femoral canal (Talini et al. 2015 [4]). Due to anatomic location of the appendix, de Garengeot hernias are most often seen on the right. Incarceration of the appendix is a clear etiology for appendicitis secondary to ischemia. Conclusion: Full preoperative workup for a femoral hernia often fails to diagnose the presence of the appendix within the hernia. It is important to have a high clinical suspicion for a de Garengeot's hernia in patients with incarcerated or strangulated right femoral hernias.